The Communicative Role of Official Spokespersons for Saudi Ministries on the X Platform in Light of Grunig and Hunt’s Public Relations Models: An Analytical Study of the Ministries of Commerce and Health - فيصل بن مونس العنزي (International Journal of Social Communication, 2025)
This study aimed to reveal the nature of the communicative role of spokespersons for the Saudi Ministries of Commerce and Health on the X platform, in light of Grunig and Hunt's public relations models. It relied on a content analysis methodology using the website (https://socialbearing.com/), where approximately 200 tweets from each spokesperson were analyzed. Results revealed an almost exclusive use of Arabic in post writing or design, along with a diversity in content forms (text, images, video) that reflects each ministry's tasks and objectives, and a strategic deployment of tags (hashtags) to enhance dissemination and guide public discourse. Analysis also showed a sharp decline in the direct interaction rate of spokespersons with audience inquiries (around 3%), which confirms a one-way communication pattern, as the findings indicated that the communicative role of the spokespersons falls under the Public Information Model, which focuses on disseminating information and facts without attention to feedback. The study recommended diversifying content and languages, fostering continuous interaction, leveraging digital analysis tools, and striving towards two-way communication models to build sustainable relationships with the public